(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Now a days online shopping is increasing rapidly.Online shopping makes easy and takes less time.Inonline shopping, we prefer the products mainly based on the reviews.By reading reviews of the product we decide the quality of product. Even though it is a very good product we may take to prefer because of reviews of the product.so it is very difficult to buy the product in online.one negative review makes the wrong impression on the product.So,It is difficult to find which is fake review and which one is Original. So,Inorder to find the fake reviews we proposed Online products Fake review Monitoring and Removal system.This system helps the customers shopping easy and takes less time to read the genuine reviews on the products.